The crisis of Islamic masculinities - De Sondy, Amanullah (London : Bloomsbury Academic, 2014)
'Rigid notions of masculinity are causing crisis in the global Islamic community.These are articulated from the Qur'an, its commentary, historical precedents and societal, religious and familial obligations. Some Muslims who don't agree with narrow constructs of manliness feel forced to consider themselves secular and therefore outside the religious community.In order to evaluate whether there really is only one valid, ideal Islamic masculinity, The Crisis of Islamic Masculinities explores key figures of the Qur'an and Indian-Pakistani Islamic history, and exposes the precariousness of tight constraints on Islamic manhood. By examining Qur'anic arguments and the strict social responsibilities advocated along with narrow Islamic masculinities, Amanullah De Sondy shows that God and women (to whom Muslim men relate but are different from) often act as foils for the construction of masculinity. He argues the constrainers of masculinity have used God and women to think with and to dominate through and that rigid gender roles are the product of a misguided enterprise: the highly personal relationship between humans and God does not lend itself to the organization of society, because that relationship cannot be typified and replicated. Discussions and debates surrounding Islamic masculinities are quickly finding their place in the study of Islam and Muslims, and The Crisis of Islamic Masculinities makes a vital contribution to this emerging field'--
Introduction -- 1.The Knot Mawdudi Tied -- 2. Feminists' Nonothering Hermeneutics -- 3. The Failed Search for a Single Qur'anic Masculinity -- 4. Mirza Ghalib's Hedonistic Challenge -- 5.Sufism's Beloved Subversion -- Conclusion.
Includes bibliographical references (pages 217-228) and index.
Keywords: Masculinity -- Islamic countries; Muslim men; Sex role -- Islamic countries